Bridging the Gap: The Role of Education and Digital Technologies in Revolutionizing Livestock Farming for Sustainability and Resilience - Nur Amlya Abd Majid; Mohd Fahmi Mohamad Amran; Muhammad Fairuz Abd Rauf; Lim Seong Pek; Suziyanti Marjudi; Puteri Nor Ellyza Nohuddin; Kemal Farouq Mauladi (The Science and Information Organization, 2026)
Indexed by (Tier 2)